Ubilical artery Doppler velocimetry diagnostic evaluation in predicting perinatal outcome in high risk pregnancies - Urviola, Richard (2015)
OBJETIVE: To evaluate the usefulness and predictive ability of the umbilical artery Doppler velocimetry in relation to adverse perinatal outcomes in high risk pregnancy. DESIGN: Prospective observational longitudinal study. MATERIALS AND METHODS: 72 pregnant women at high risk between 28 and 41 weeks was selected, determining resistance indices, relative absence systole-diastole and end-diastolic flow using pulsed color Doppler imaging equipment Aloka SSD 1700. The adverse perinatal outcomes They were categorized and related umbilical Doppler examination. RESULTS: umbilical flow abnormality was found in 38.9% of cases, with increased risk (p <0.01) for IUGR and cesareans for fetal distress, predicting IUGR fetuses (70.8%), stay in UCI over 8 days (66.7%) and neonatal acidemia (65.3%). The overall accuracy of systole-diastole ratio was 66.7%. The absence of end diastolic flow was associated with perinatal death in 94.4%. CONCLUSION: The umbilical artery Doppler velocimetry has good predictive capacity only for IUGR, caesarean section for fetal distress, prolonged stay in the ICU and neonatal acidemia, with the absence of end diastolic flow a strong predictor of perinatal death.